Iniquities - Nelson, Rose (East Carolina University, 2015)
This thesis is a representative collection of short stories that I have written as part of my Master's requirements. The four pieces included demonstrate the overarching style, length, and major themes of much of my recent work, and are, thereby, connected in these areas. The main purpose of the selection is to show the culmination of two years of study and practice in the broad category of creative writing. These sample works also exemplify the type of fiction I hope to market to various literary outlets in the near future.
Keywords: American literature; Creative writing; Fiction; Disabled veterans' families--Fiction; Rape victims--Fiction; Forgiveness--Fiction; Child abuse--Fiction